Biological and ecological traits that assist establishment of alien invasive insects - Peacock, L.; Worner, S.P. (New Zealand Plant Protection, 2008)
In this study the biological and ecological traits of two groups of phytophagous insect pests were examined to determine attributes that may influence establishment in New Zealand Biological and ecological attributes of a group of insect species that is established in New Zealand were compared with species that are not currently established It was found that the species established in New Zealand had a significantly wider host plant range than species that have not established The lower developmental threshold temperature was on average 4C lower for established species compared with nonestablished species These data suggest that species that establish well in New Zealand have a wide host range and can tolerate lower temperatures compared with those that have not established